Art + religion in the 21st century - Rosen, Aaron (London, England : Thames & Hudson, 2015)
Contrary to the expectations of 20th-century rationalists, religion has not faded away in the 21st century, but roared back onto the scene with renewed vitality. This survey shows how religious themes and images continue to permeate the work of contemporary artists from across the globe. Some exploit the shock potential of religious imagery, but many also reflect deeply on spiritual matters. The introduction outlines the debates and controversies that the art-religion connection has precipitated throughout history. Each of the ten chapters opens by introducing a theme, followed by a selection of works of art that develop that theme. The book encompasses a wide range of media and genres, from sculpture to street art, and considers faith in its broadest sense from Islam and Christianity to Aboriginal mythology and meditation.
Part I. People of the image? In the beginning ; Sweet Jesus! -- Part II. Wonder. The sublime ; Heaven and earthworks -- Part III. Cultural identities. Creative differences ; Conflicting images -- Part IV. Ritual. Performance rites ; Structure and loss -- Part V. Indwelling. Embodiment ; Galleries and sanctuaries.
Includes bibliographical references (pages 248-252) and index.
Keywords: Art and religion; Art, Modern -- 21st century